Guru Pendidikan Agama Hindu Sebagai Mediator Dalam Peningkatan Kualitas Karakter Siswa di SMK Negeri 1 Mataram - Putri, Ni Made Desi Swardani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Hindu religious education teachers are at the forefront in improving the quality of student character, especially for Hindu students during their study period. So Hindu religious education teachers must have knowledge and abilities on how to improve the quality of character and of course have quality character that can be emulated by their students. This research aims to increase understanding of the importance of Hindu religious education teachers as mediators in improving the quality of student character. There are three methods used in this research, namely the interview method, direct observation method, and documentation method. The importance of the results of this research is as a guide for prospective Hindu religious education teachers in the future in improving the quality of character possessed by students.